Use of Frame Running for Adolescent Athletes With Movement Challenges: Study of Feasibility to Support Health and Participation - Sukal-Moulton, Theresa; Egan, Tara; Johnson, Larke; Lein, Crystal; Gaebler-Spira, Deborah (Frontiers in Sports and Active Living, 2022)
Children and adolescents with movement challenges have lower instances of physical activity and longer time spent in sedentary behaviors compared to children with typical development. The purpose of this study was to investigate the feasibility of a sport-based youth development running program modified for accessibility using a running frame and to evaluate initial evidence for its efficacy on endurance and functional strength. We completed four 8-week seasons (2–3 times per week) in a combination of 3 different formats by season: online remote (winter and spring), in person in a community park (winter, spring, and summer), and in person in an afterschool setting (autumn). Participants included 13 athletes (average age 14.46 years, range 8–18 years, 4 females), who collectively completed 22 season blocks. Diagnoses included cerebral palsy (n = 10), arthrogryposis (n = 1), Dandy-Walker malformation (n = 1), and transverse myelitis (n = 1). In all settings, participants engaged in activities of social emotional learning, cardiovascular endurance, and muscle strengthening in a progressive manner. We found that each season format was feasible to administer with high attendance rates (76–97%) and positive qualitative feedback from athletes. In addition, promising average improvements in motor performance across a season (6 min frame running test, 170 m; timed up and go test, 8.44 s; five times sit to stand, 14.1 s; and Goal Attainment Scale, t = 65.01) were identified in the pilot data of this non-randomized cohort. Training in any of the proposed settings with an overall goal of completing a community race in a running frame is feasible and warrants further study.